Membangun Pesantren Berdaya Saing Global: Sinergi antara Tradisi dan Modernisasi - Astuti, Ruli; Nisak, Nur Maslikhatun (Sekolah Tinggi Agama Islam Al-Muntahy, 2024)
The synergy between tradition and modernization is essential for the development of pesantren that can compete on a global scale. This article aims to analyze the development of the quality of pesantren to have global competitiveness, as well as their efforts in synergizing tradition and modernization. This study uses the literature review to examine pesantren's methods for increasing global competitiveness, as well as their efforts to align tradition with modernization. This study was carried out by gathering, analyzing, and synthesizing data from a variety of relevant literature sources, such as books, scientific journals, articles, research reports, and so on. The findings of this study reveal that pesantren play a critical role in producing competitive graduates in the age of globalization. As a result, efforts must be made to improve educational quality by addressing curriculum components, teaching personnel, infrastructure, and a more professional management system. To remain relevant in a changing world, pesantren must be modernized while retaining traditional values. This step allows pesantren to continue developing as an excellent, adaptable, and innovative educational institution addressing global concerns.